2018
DOI: 10.2478/jlecol-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Land Use Land Cover Dynamics Using GIS and Remote sensing in Central Highlands of Ethiopia

Abstract: Assessing and quantifying the current forest resources status underpins sustainable forest resources planning and management. To this end, this study was conducted to analyze the dynamics of land use cover change (LUCC) and explore their drivers at the central highlands of Dry Afromontane Chilimo-Gaji forest for the study period (1973-2015) under consideration. The result of the study indicated that landscape trends have occurred in Chilimo-Gaji forest over the last 43 years and five classes of LUCC namely shr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
7
14
0
Order By: Relevance
“…Figure 3 shows that the lake catchment and lowland areas are characterized by dense cultivation, densely populated, and treeless dominated by shrub and grassland. The area under study was found that the bare/shrub/grassland increased from 1989 to 2019, which aligns with the findings of Daniel (2008), Tolessa et al (2017), and Siraj et al (2018). The increase in bare/shrub/grassland is attributed to the high rate of forest reserve conversion into bare land (plate 1a) as the demand for charcoal production and agricultural activities increases.…”
Section: The Accuracy Assessment and Lulc Classessupporting
confidence: 81%
“…Figure 3 shows that the lake catchment and lowland areas are characterized by dense cultivation, densely populated, and treeless dominated by shrub and grassland. The area under study was found that the bare/shrub/grassland increased from 1989 to 2019, which aligns with the findings of Daniel (2008), Tolessa et al (2017), and Siraj et al (2018). The increase in bare/shrub/grassland is attributed to the high rate of forest reserve conversion into bare land (plate 1a) as the demand for charcoal production and agricultural activities increases.…”
Section: The Accuracy Assessment and Lulc Classessupporting
confidence: 81%
“…Between 1986 and 2020, the highest increase in the percentage of cropland (74%) has been noted, which is related to a rise in small-scale farming ( Table 5 ). Previous researches reported a 44%, 36.4%, and 65% rise in cultivated land by [ 91 , 92 ] respectively. When subsistence farming is not supported by modern technology, agricultural yield boosting can be attained by the addition of parcels of land under farming, and this is exactly seen in the current study area [ 90 , 93 , 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deforestation and degradation are the causes of forest cover loss in Ethiopia which has its origin in a cascade of events [12]. e Geometric population growth of Ethiopia resulted in rural demand for agricultural lands [13], which in turn led to the expansion of cultivated fields at the expense of the forest and other land use types such as grazing and shrub lands [14,15]. e Ethiopian vegetations, particularly the forest resources, are under severe pressure as a consequence of inhabitants need of more farm land for agriculture and grazing lands for their livestock.…”
Section: Introductionmentioning
confidence: 99%